Water temperature, voluntary drinking and fluid balance in dehydrated Taekwondo athletes - Khamnei, S.; Hosseinlou, A.; Zamanlu, M. (Journal of Sports Science & Medicine, 2011)
Voluntary drinking is one of the major determiners of rehydration, especially as regards exercise or workout in the heat. The present study undertakes to search for the effect of voluntary intake of water with different temperatures on fluid balance in Taekwondo athletes. Six young healthy male Taekwondo athletes were dehydrated by moderate exercise in a chamber with ambient temperature at 38-40°C and relative humidity between 20-30%. On four separate days they were allowed to drink ad libitum plane water with the four temperatures of 5, 16, 26, and 58°C, after dehydration. The volume of voluntary drinking and weight change was measured; then the primary percentage of dehydration, sweat loss, fluid deficit and involuntary dehydration were calculated. Voluntary drinking of water proved to be statistically different in the presented temperatures. Water at 16°C involved the greatest intake, while fluid deficit and involuntary dehydration were the lowest. Intake of water in the 5°C trial significantly correlated with the subject's plasma osmolality change after dehydration, yet it showed no significant correlation with weight loss. In conclusion, by way of achieving more voluntary intake of water and better fluid state, recommending cool water (~16°C) for athletes is in order. Unlike the publicly held view, drinking cold water (~5°C) does not improve voluntary drinking and hydration status.